2021
DOI: 10.3390/ma14071815
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Model for Energy Propagation in Disordered Granular Chains

Abstract: Energy transfer is one of the essentials of mechanical wave propagation (along with momentum transport). Here, it is studied in disordered one-dimensional model systems mimicking force-chains in real systems. The pre-stressed random masses (other types of disorder lead to qualitatively similar behavior) interact through (linearized) Hertzian repulsive forces, which allows solving the deterministic problem analytically. The main goal, a simpler, faster stochastic model for energy propagation, is presented in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…P-waves are compressional or longitudinal waves that oscillate the ground back and forth along the direction of wave travel, in much the same way that sound waves (which are also compressional) move air back and forth as the waves travel from the sound source to a sound receiver. In a longitudinal wave, the particle displacement is parallel to the direction of wave propagation [30,32,33,47,53].…”
Section: Stiffness Determination Based On Wave Propagation Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…P-waves are compressional or longitudinal waves that oscillate the ground back and forth along the direction of wave travel, in much the same way that sound waves (which are also compressional) move air back and forth as the waves travel from the sound source to a sound receiver. In a longitudinal wave, the particle displacement is parallel to the direction of wave propagation [30,32,33,47,53].…”
Section: Stiffness Determination Based On Wave Propagation Measurementmentioning
confidence: 99%
“…Granular matter has a heterogeneous nature, this is expressed as force chains through the medium. These force chains spread the forces through the contact with another particle [53,54]. This causes that neighboring particles could have forces of different magnitudes and nonisotropic distributions of stress throughout the medium [2].…”
Section: Image Characterizationmentioning
confidence: 99%
“…For a better understanding of the sound in granular media, theoretical models incorporating the rotational degrees of freedom in the microstructure are crucial [7], e.g., the model of one-dimensional granular chains [8,9]. In two or three dimensions, theoretical models of granular crystals have been extensively developed [7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Binary granular materials including sand-fiber composites, display significant complexity in their behavior with competitive mechanisms to be encountered with respect to energy transport and dissipation as recent theoretical and experimental studies have shown [40][41][42]. This adds further difficulties in the constitutive modeling of these systems compared, for example, to the analysis of soil-planar block interactions.…”
Section: Introductionmentioning
confidence: 99%